STUDY ON STAKEHOLDER ENGAGEMENT AND COMMUNICATION IN DEVELOPING SUSTAINABLE TOURISM IN INDONESIA - Prayudi, . (PEOPLE: International Journal of Social Sciences, 2018)
This paper examines how stakeholder engagement and communication had been used to identify and manage stakeholders in the development of sustainable tourism. Stakeholder engagement is a way to build relationship with stakeholders that emphasizes two-way communication to achieve intended outcomes. The study used qualitative research method. In this study, primary and secondary stakeholders were identified through analysis of their level of interest and influence. Later, the form of engagement and communication was determined for every stakeholder. Through this process, a forum that based on two-way communication was formed and consisted of relevant stakeholders. This forum helped identify supporting and challenging factors in developing sustainable tourism in Indonesia. Some programs that combine social, economic and environment factors were constructed to build a sustainable tourist destination. One of the challenges is how to change the mindset of villagers or local people of the benefit of turning their village as tourist destination whilst preserving the nature and local wisdom.